(untitled) (Journal of Medical & Health Sciences Review, 2024)
Background: Traumatic urethral injuries are a severe urological issue that frequently arises from pelvic fractures or direct trauma to the perineum. Because the anterior and posterior urethras differ anatomically, surgical reconstructive techniques are fundamentally different. A thorough comparative analysis of the therapeutic approaches for these various damage patterns is necessary to optimize patient care, particularly in light of evolving surgical techniques and a growing focus on functional outcomes. Objective: This study aims to systematically investigate the etiology, surgical techniques, success rates, and complication profiles of anterior and posterior urethral repair following traumatic injury. The goal is to describe the specific roles and clinical considerations for reconstruction in each anatomical region in order to facilitate evidence-based surgical decision making. Methods: A systematic, comparative review of the literature was conducted. Peer-reviewed scientific articles, well-known urology manuals, and guidelines for medical practice were the sources of the data. The analysis’s main concerns were anatomical ideas, the timing of the operation, surgical techniques (primary anastomosis and excision versus substitution urethroplasty), and quantitative outcomes including erectile dysfunction, urine incontinence, stricture recurrence, and continuous patency. Result: The analysis’s findings demonstrate a glaring disparity: While excision and primary anastomosis (EPA) are commonly used in anterior urethral repair, primarily for bulbar strictures resulting from straddle injuries, with long-term success rates of 85–95%, the majority of complications are minor and have little impact on continence. The more complex posterior urethral reconstruction for pelvic fracture urethral injuries (PFUI) uses delayed perineal anastomosis, which has an even higher risk of serious functional issues, including fresh or exacerbated erectile dysfunction (5–15%) and urine incontinence (5–10%), which are often layered on top of a high rate of pre-existing ED from the initial shock. Conclusion: The role of urethral reconstruction in anterior and posterior injuries is essentially different. Anterior repair is a very successful method for restoring urethral patency with little morbidity. The challenging process of posterior restoration entails reestablishing continuity while navigating a hazardous anatomical region in order to preserve sexual and urine function. The surgical approach needs to be tailored to the injury site; posterior injuries necessitate specialized understanding to optimize quality of life in the long run.